Closed-loop vasopressor systems for hemodynamic stability during cesarean delivery and maternal and neonatal outcomes: a systematic review and meta-analysis - M.J. Khan (22437616) (2025)
Background Closed-loop vasopressor systems automate vasopressor administration using real-time hemodynamic biofeedback; clinical equipoise exists between closed-loop vasopressor systems and manual vasopressor titration. This review evaluates the performance and hemodynamic outcomes of closed-loop vasopressor systems vs. manual titration in cesarean delivery under spinal anesthesia. Methods Included studies compared closed-loop vasopressor systems with manual vasopressor administration for spinal hypotension in cesarean delivery. Primary outcomes were closed-loop vasopressor systems performance and hemodynamic measures. Performance was assessed with median performance error, median absolute performance error, wobble (intraindividual variation in performance error) and divergence (performance error over time). Meta-analyses were conducted for RCTs and observational studies separately. Risk of bias was assessed using Cochrane methodology. Data were reported as risk ratio (RR) or mean difference (MD) with 95 % confidence intervals (CI). Results Seven studies (n = 864) were included. In three RCTs (n = 654), wobble (MD −0.66 %; 95 % CI −1.29 to −0.02; P = 0.04), hypotension incidence (RR 0.67; 95 % CI 0.55 to 0.82; P < 0.01), and the highest and lowest systolic blood pressures values (MD −4.05 mmHg; 95 % CI −7.03 to −1.06; P < 0.01 and MD 5.39 mmHg; 95 % CI 2.17 to 8.60; P < 0.01, respectively) were minimized with closed-loop vasopressor systems, but no significant differences were observed in other primary outcomes. Maternal nausea was reduced with closed-loop vasopressor systems (RR 0.47; 95 % CI 0.26 to 0.85; P = 0.01; moderate quality of evidence). In four observational studies (n = 210), the pooled values for median absolute performance error, wobble, divergence of the system, hypotension incidence, highest and lowest systolic blood pressures, highest and lowest heart rates, total fluids, total phenylephrine and ephedrine dosages were statistically significant. Risk of bias was low to moderate for all studies. Conclusion Closed-loop vasopressor systems may improve systolic blood pressure fluctuations in cesarean deliveries with spinal anesthesia compared to manually adjusted vasopressor dosing; however, more high-quality evidence is needed. Other Information Published in: International Journal of Obstetric Anesthesia License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijoa.2025.104768